Primary Care Physicians' Concerns May Affect Adolescents' Access to Intrauterine Contraception - Susan E Rubin; Giselle Campos; Susan Markens (SAGE Publishing, 2013)
Purpose: Although the intrauterine device (IUD) may be safely used in adolescents, few US adolescents use IUDs. Increasing IUD use in adolescents can decrease pregnancy rates. Primary care providers' clinical practices many be one of the many barriers to increasing adolescents access to IUDs. We explored primary care physicians' (PCPs) approaches to contraception counseling with adolescents, focusing on their views about who would be appropriate IUD candidates. Methods: Phone interviews were conducted with 28 urban family physicians, pediatricians, and obstetrician-gynecologists. Using standard qualitative techniques, we developed coding template and applied codes. Results: Most respondents have a patient-centered general contraceptive counseling approach. However, when considering IUDs many PCPs describe more paternalistic counseling. For example, although many respondents believe adolescents' primary concern is pregnancy prevention, many PCPs prioritize sexually transmitted infection (STI) prevention and thus would not offer an IUD. Attributes PCPs associate with an appropriate IUD candidate include responsibility, reliability, maturity, and monogamy. Conclusion: Our findings suggest that when considering IUDs for adolescents some PCPs' subjective assessment of adolescent sexual behavior, attitudes about STI risk factors and use of overly restrictive IUD eligibility criteria impede adolescent's IUD access. Education around best practices may be insufficient to counterbalance attitudes concerning adolescent sexuality and STI risk; there is also a need to identify and discuss PCPs potential biases or assumptions affecting contraception counseling.